2010
DOI: 10.1002/iub.307
|View full text |Cite
|
Sign up to set email alerts
|

Porcine induced pluripotent stem cells may bridge the gap between mouse and human iPS

Abstract: SummaryRecently, three independent laboratories reported the generation of induced pluripotent stem cells (iPSCs) from pig (Sus scrofa). This finding sums to the growing list of species (mouse, human, monkey, and rat, in this order) for which successful reprogramming using exogenous factors has been achieved, and multiple others are possibly forthcoming. But apart from demonstrating the universality of the network identified by Shinya Yamanaka, what makes the porcine model so special? On one side, pigs are an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Advances in pig genome annotation, genetic modification (GM) of pig cells and somatic cell nuclear transfer (SCNT), have facilitated the generation of GM pigs for various biomedical applications. However, the establishment of porcine embryonic stem cells (ESCs) has proven elusive, despite decades of intense trials, and a similar lack of success has been observed with other ungulate species (Esteban et al 2010). The generation of GM pigs primarily relies on homologous recombination in somatic cells, followed by SCNT.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in pig genome annotation, genetic modification (GM) of pig cells and somatic cell nuclear transfer (SCNT), have facilitated the generation of GM pigs for various biomedical applications. However, the establishment of porcine embryonic stem cells (ESCs) has proven elusive, despite decades of intense trials, and a similar lack of success has been observed with other ungulate species (Esteban et al 2010). The generation of GM pigs primarily relies on homologous recombination in somatic cells, followed by SCNT.…”
Section: Introductionmentioning
confidence: 99%
“…The iPSC models will have an effect on human iPSCs research, because they may not only serve to bridge murine and human iPSCs as model systems [112] but also help --in a contrast and compare approach --to dissect transcription factor networks and signalling pathways in pluripotency and differentiation.…”
Section: Schambach Cantz Baum and Cathomenmentioning
confidence: 99%
“…Lines of iPSCs have been generated from some domesticated ungulates, such as sheep [90,91] , pigs [87,92,93] and cattle [94,95] . Porcine iPSCs have been produced in many laboratories using various induction methods and show pluripotency to some degree [59,93,96,97] .…”
Section: Progress On Inducing Pluripotent Stem Cells Of Pig and Othermentioning
confidence: 99%
“…Porcine iPSCs have been produced in many laboratories using various induction methods and show pluripotency to some degree [59,93,96,97] . Porcine iPSCs could pass the test of germline chimera production at the molecular genotyping levels using PCR [42,98] , but stable chimerism remains to be determined.…”
Section: Progress On Inducing Pluripotent Stem Cells Of Pig and Othermentioning
confidence: 99%